Dissecting the Effects of Aldosterone and Hypokalemia on the Epithelial Na+ Channel and the NaCl Cotransporter - Kristensen, Mathias; Fenton, Robert A.; Poulsen, Søren B. (Frontiers in Physiology, 2022)
Primary hyperaldosteronism (PA) is characterized by aldosterone excess and hypertension. This may be linked to increased renal Na+ reabsorption via the epithelial Na+ channel (ENaC) and the NaCl cotransporter (NCC). The majority of PA patients have normal plasma K+ levels, but a subset of cases are associated with hypokalemia. High NCC levels observed in long-term studies with aldosterone-infused rodents have been attributed to direct effects of aldosterone. Aldosterone can also increase active phosphorylated NCC (pT58-NCC) acutely. However, direct effects of aldosterone on NCC have been contested by recent studies indicating that it is rather an indirect effect of hypokalemia. We therefore set out to determine isolated long-term aldosterone and K+ effects on ENaC and NCC using various in vivo and ex vivo approaches. In mice, aldosterone-induced hypokalemia was prevented by simultaneous amiloride infusion, coupled to increased cleavage of α- and γENaC but no effect on NCC. Regression analyses of in vivo data showed a positive correlation between aldosterone/K+ and αENaC but a negative correlation with NCC and pT58-NCC. Ex vivo, exposure of kidney tubules for 21 h to aldosterone increased cleavage of αENaC and γENaC, but no effects were observed on NCC or pT58-NCC. Exposure of tubules to low K+ media reduced αENaC but increased NCC and pT58-NCC. As hypokalemia can enhance cell proliferation markers in the distal convoluted tubule (DCT), we hypothesized that aldosterone infusion would increase proliferating cell nuclear antigen (PCNA) expression. Infusion of aldosterone in mice for 6 days greatly increased PCNA expression in the DCT. Collectively, in vivo and ex vivo data suggest that both aldosterone and K+ can increase ENaC directly. In contrast, the observed increase in abundance and phosphorylation of NCC in aldosterone-infused mice is likely an indirect effect of enhanced ENaC-mediated K+ secretion and subsequent hypokalemia. Thus, it is possible that NCC may only be increased in PA when the condition is associated with hypokalemia.